An Industrial systems design study on The Chocolate Kiss Cafe - Bantola, Timothy; Butac, Aleczar; Magsuci, Kristopher; Patacsil, Miguel (College of Engineering, 2005)
An Industrial Systems Design Study was conducted on Chocolate Kiss Café, a café restaurant serving food and pastries for students and faculty in and around UP Diliman. With two branches located at the Bahay ng Alumni in the University of the Philippines Diliman, it has captured a market niche of students and faculty looking for a good place to dine. The objectives of the study was to apply the total systems approach in strategy analysis and design of this food service company; using strategic analysis techniques, key strategies performed were identified and analyzed, key problem gaps toward their company goals were acknowledged, and focusing on these problems, sound operational improvements were recommended using different industrial engineering techniques. Environmental scanning was performed using several techniques namely: Porters 5 Forces model, Seven S model, and SWOT analysis. Current strategies of the company were identified; results showed that Chocolate Kiss employs these strategies: *Establish a firm niche inside UP, *Have two branches for customer convenience, *Conduct yearly assessment of menu, *Have many sources for raw materials, *Operate with hierarchical and centralized organizational structure, with well-defined job functions, *Differentiate the menu with distinct dishes exclusive to Chocolate Kiss, *Employ a well-trained kitchen staff, *Have a clear Mission and Vision, *Foster a family atmosphere with staff. Strategic Formation techniques were then conducted to be able to identify possible strategies that can be incorporated by the company. These techniques are the grand strategy matrix, porter's generic strategy, expansion strategy and the TOWS matrix. Gap and Problem analysis was then conducted to be able to identify gaps within the company's progress toward its goals. Using the Quantitative Strategic Planning Matrix, problems and strategies were integrated to be able to come up with operational recommendations in line with key strategies that the company can focus on to better its competitive advantage over other food establishment players. The Identified Key strategies that the Company can pursue are the Concentric Diversification strategy where the company expands itself by adding new but related products and service and the Focus Strategy on Differentiation wherein the company targets a narrow market and focuses on product and service differentiation. Integrating these key strategies and the company's mission and vision, operational recommendations were then suggested where possible gaps ca be bridged in order for the company to position itself competitively in the market. These operational recommendations, with their included benefits, are as follows: *Transferring the commissary to a nearer location ? Studies showed that transferring the commissary to the suggested location can improve their service by decreasing customer waiting time, can minimize wastes and lower costs; *Branching out of The Chocolate Kiss Café ? This recommendation fulfills its vision of establishing itself in different schools and universities. By branching out in the Katipunan area, Chocolate Kiss reaches new markets and maximizes its man-power; *Expanding its service thru catering ? This recommendation fulfills unmet demands and offers another dimension to their services. In the industry where competition is stiff, expanding to catering services will give it a competitive edge against other players; *Developing a marketing department ? By developing a marketing department the Chocolate Kiss can focus on customer wants and be able to maintain food products that are in demand and to promote its new services (catering and the new branch). Implementations guidelines for the setup of these recommendations were also give